PERAN KEPEMIMPINAN SPIRITUAL DALAM MENINGKATKAN MUTU SEBUAH ORGANISASI - Mochamad Nurcholiq (Ta`Limuna: Jurnal Pendidikan Islam, 2013)
Effect on the growth of spiritual leadership and organizational commitment pruduktivitas, employee welfare and social responsibility. The growth of well-being, commitment, productivity, and social responsibility and continuous improvement will improve the organization and produce quality products and satisfactory services to customers and stakeholders. In this paper the authors want to discuss more in how the actual role of spiritual leadership in improving the quality of an organization.